Last updated at March 9, 2017 by Teachoo

Transcript

Ex9.3, 22 If the pth ,qth and rth terms of a G.P. are a, b and c, respectively. Prove that aq – r br – p cp – q = 1 We know that nth term of G.P = ARn – 1 (We are using a, r in the question, so we use A for first term and R for common ratio) It is given that pth term of G.P = a Ap = a ARp–1 = a a = ARp–1 aq – r = ("ARp–1")q – r We need to show that aq – r br – p cp – q = 1 Also, qth term of G.P = b Aq = b ARq–1 = b b = ARq–1 br – p = (ARq – 1)r – p & rth term of G.P = c Ar = c ARr–1 = c c = ARr – 1 cp – q = (ARr – 1)p – q Now, our equations are aq – r = ("ARp–1")q – r …(1) br – p = (ARq – 1)r – p …(2) & cp – q = (ARr – 1)p – q …(3) Taking L.H.S. aq – r br – p cp – q Putting values from (1), (2) & (3) = ("ARp–1")q – r × (ARq – 1)r – p × (ARr – 1)p – q = "Aq – r R(p–1")(q – r) × "Ar – p R(q–1")(r – p) × "Ap – q R(r–1")(p – q) = "Aq – r Ar – p Ap – q " × "R(p–1")(q – r) "R(q–1")(r – p) "R(r–1")(p – q) = A(q – r) + (r – p) + (p – q) × R(p – 1) (q - r) + (q – 1) ( r - p) + (r – 1) ( p-q) = A(q – r) + (r – p) + (p – q) × Rp(q – r ) – 1(q – r) + q( r – p) – 1(r – p) +r(p – q) – 1( p – q) = A(q – q) + (r – r) + (p – p) × Rpq – pr – q + r + qr – qp – r + p + rp – qr – p + q = A0 × R pq – pq – q + q + r – r + p – p + qr – qr + qp – qr = A0 × R0 = 1 × 1 = 1 = R.H.S Thus, L.H.S = R.H.S Hence proved

Ex 9.3, 1

Ex 9.3, 2

Ex 9.3, 3 Important

Ex 9.3, 4

Ex 9.3, 5

Ex 9.3, 6

Ex 9.3, 7

Ex 9.3, 8

Ex 9.3, 9

Ex 9.3, 10

Ex 9.3, 11 Important

Ex 9.3, 12

Ex 9.3, 13

Ex 9.3, 14

Ex 9.3, 15

Ex 9.3, 16

Ex 9.3, 17 Important

Ex 9.3, 18 Important

Ex 9.3, 19

Ex 9.3, 20

Ex 9.3, 21

Ex 9.3, 22 Important You are here

Ex 9.3, 23

Ex 9.3, 24

Ex 9.3, 25

Ex 9.3, 26

Ex 9.3, 27 Important

Ex 9.3, 28 Important

Ex 9.3, 29 Important

Ex 9.3, 30

Ex 9.3, 31

Ex 9.3, 32

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He provides courses for Mathematics from Class 9 to 12. You can ask questions here.